Design of Arduino-Based Automatic Motor Wire Rewinding System - Parningotan, Jasman Wanfaber; Napitupulu, Janter; Sholeha, Dewi; Ammar, Muhammad Khoirul (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
In the industrial world, the motor winding process is one of the important stages in the manufacture and rewinding of electric motors. Many electric motors are damaged and even the motor can burn because in the operation of electric motors often serve loads that exceed the limits of the motor's ability (overload), contaminated with foreign objects, age, bearing problems, which can cause the effect of changing the current, causing heat which if left for a long time can cause burning of the motor wire winding. With the damage to the motor wire winding, a cost-effective solution that can be done is to rewind the motor wire. the motor rewinding process is carried out so that the winding can return to normal and work properly. The research was conducted using the experimental method. In the research, an automatic rolling device using an Arduino microcontroller was designed. The test results that the system can function normally in the process of inputting the value of the number of rolls, rolling driven by stepper motors and LCD has functioned properly in displaying each data on the system designed.